Implementation of Labor Protection Policy in Bone Bolango Regency, Gorontalo Province - Hunawa, Robby; Podungge, Abdul Wahab; Nuna, Muten; Tabo, Sarfan; Polinggapo, Jefri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In order to protect occupational safety and health in carrying out work, such protection must be in accordance with applicable laws and regulations. For workers/laborers, with the guarantee of occupational safety protection, it will create a peaceful working atmosphere so that workers/laborers will be able to focus their attention on the work as much as possible without worrying about being hit by a work accident at any time. This study was conducted to determine and analyze the implementation of labor protection policies in Bone Bolango Regency, Gorontalo Province. This study uses a qualitative method with a descriptive approach, namely research that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of the study have shown that the labor protection policy program implemented by the Bone Bolango Regency Government has been running well in accordance with the provisions of applicable laws and regulations. This can be seen from several protection indicators used, namely: 1) Economic protection; 2) Social protection; and 3) Technical protection. Based on the results of the study, it has been shown that these three forms of protection provided can guarantee the welfare of workers and the community who participate in the protection program. Therefore, the Bone Bolango Regency Government continues to maximize the labor protection program by continuously monitoring and evaluating various labor business activities, so that income and welfare for workers and the community in Bone Bolango Regency continue to increase in the future.